Evaluation of thymic tumors with 18F-FDG PET-CT: A pictorial review. (February 2013) - Sharma, Punit; Singhal, Abhinav; Kumar, Arvind; Bal, Chandrasekhar; Malhotra, Arun; Kumar, Rakesh
Thymic tumors represent a broad spectrum of neoplastic disorders and pose considerable diagnostic difficulties. A non-invasive imaging study to determine the nature of thymic lesions can have significant impact on management of such tumors. 18F-flurorodeoxyglucose (18F-FDG) positron emission tomography-computed tomography (PET-CT) has shown promising results in characterization of thymic tumors. The objective of this article is to provide an illustrative tutorial highlighting the clinical utility of 18F-FDG PET-CT imaging in patients with thymic tumors. We have pictorially depicted the 18F-FDG PET-CT salient imaging characteristics of various thymic tumors, both epithelial and non-epithelial. Also discussed is the dynamic physiology of thymus gland which is to be kept in mind when evaluating thymic pathology on 18F-FDG PET-CT, as it can lead to interpretative pitfalls.